If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3) * 2 = (x + -2) * 3 Reorder the terms: (3 + x) * 2 = (x + -2) * 3 Reorder the terms for easier multiplication: 2(3 + x) = (x + -2) * 3 (3 * 2 + x * 2) = (x + -2) * 3 (6 + 2x) = (x + -2) * 3 Reorder the terms: 6 + 2x = (-2 + x) * 3 Reorder the terms for easier multiplication: 6 + 2x = 3(-2 + x) 6 + 2x = (-2 * 3 + x * 3) 6 + 2x = (-6 + 3x) Solving 6 + 2x = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + 2x + -3x = -6 + 3x + -3x Combine like terms: 2x + -3x = -1x 6 + -1x = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + -1x = -6 + 0 6 + -1x = -6 Add '-6' to each side of the equation. 6 + -6 + -1x = -6 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = -6 + -6 -1x = -6 + -6 Combine like terms: -6 + -6 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| 6.7*4.2= | | -89+8x=177-6x | | Y=3.5*-3+6 | | -39+2x=13 | | Y=3.5*8+6 | | x^2-k(2x-5)=2x-5 | | (x+3)(x-3)(2x+1)= | | -91+6x=-10x+133 | | 1/2(4x-6)=7 | | [-15(-1.5)]+[(-2.5)*1.25]= | | [-15(-15)]+[(-2.5)*1.25]= | | 25x^2-18x-200=0 | | 2x^5+17x^4+45x^3+28x^2-44x+48=0 | | 0.67x=18 | | 2(x-2)=x+14 | | 0.75z-1=0.25z+2 | | 0.01x-3=4 | | 0.3x-5=0.1x+3 | | -0.25x=-5 | | -0.25=-5 | | 1/4(8x-24) | | q=1000-.4p | | 3x(3xy-5y)= | | 6-(5x/2(7-3x)/2 | | -4=0.4x | | 8(x-2)=7(x-1)-12+x | | 0.15x+27=31.5 | | 3x-17=52 | | (x-5)(2x-14)=4(3x-21) | | p^4/p^3 | | -7n(-1+3a)=5(3-5a) | | 20-5x=75 |